2018
DOI: 10.1101/288365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of mitochondrial ferredoxin 1 (FDX1) prevents adaptation to proteotoxic stress

Abstract: SUMMARYThe mechanisms used by cancer cells to resist the severe disruption in protein homeostasis caused by proteasome inhibitors remain obscure. Here, we show this resistance correlates with a metabolic shift from glycolysis to oxidative phosphorylation (OXPHOS). Employing small molecule screens, we identified a striking overlap between compounds that preferentially impede the growth of proteasome inhibitor-resistant cancer cells and those that block the growth of high OXPHOS cells. Elesclomol potently exhibi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 88 publications
3
33
0
Order By: Relevance
“…FDX1 encodes a small iron-sulfur protein that participates in the reduction in mitochondrial cytochrome and the synthesis of various steroid hormones (Sheftel et al, 2010;Strushkevich et al, 2011). Also, FDX1 can augment the copper-dependent cell death induced by elesclomol and may provide a new idea for increasing the efficacy of several cancer-targeting agents (Tsvetkov et al, 2019). Next, we focused on FDX1 and explored its function in LUAD.…”
Section: Resultsmentioning
confidence: 99%
“…FDX1 encodes a small iron-sulfur protein that participates in the reduction in mitochondrial cytochrome and the synthesis of various steroid hormones (Sheftel et al, 2010;Strushkevich et al, 2011). Also, FDX1 can augment the copper-dependent cell death induced by elesclomol and may provide a new idea for increasing the efficacy of several cancer-targeting agents (Tsvetkov et al, 2019). Next, we focused on FDX1 and explored its function in LUAD.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in terms of tumor chemotherapy, there were few studies on the relationship between FDX1 and tumor resistance. Only Tsvetkov et al (Tsvetkov et al, 2019) found that FDX1 was highly associated with the proteasome inhibitor elesclomol and a direct target of elesclomol. However, no correlation was found between the two in our study, which might be related to the low number of cell lines in the CellMiner database and the slow update of experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that copper commonly exhibited anti-tumor effects via the formation of metal chelators and ionophores (Steinbrueck et al, 2020). For the first time, Tsvetkov et al defined Cudependent cytotoxicity, which leads to regulated cell death (RCD), as "cuproptosis" (Tsvetkov et al, 2019;Tsvetkov et al, 2022). Previous research suggested that copper-dependent cell death was correlated with the progression and treatment of glioma (Buccarelli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%